Induction of phospholipase A2 group 4C by HCV infection regulates lipid droplet formation - Masahiko Ito; Jie Liu; Masayoshi Fukasawa; Koji Tsutsumi; Yumi Kanegae; Mitsutoshi Setou; Michinori Kohara; Tetsuro Suzuki (JHEP Reports)
Background & Aims: Hepatic steatosis, characterized by lipid accumulation in hepatocytes, is a key diagnostic feature in patients with chronic hepatitis C virus (HCV) infection. This study aimed to clarify the involvement of phospholipid metabolic pathways in the pathogenesis of HCV-induced steatosis. Methods: The expression and distribution of lipid species in the livers of human liver chimeric mice were analyzed using imaging mass spectrometry. Triglyceride accumulation and lipid droplet formation were studied in phospholipase A2 group 4C (PLA2G4C) knockout or overexpressing cells. Results: Imaging mass spectrometry of the infected mouse model revealed increased lysophosphatidylcholine levels and decreased phosphatidylcholine levels in HCV-positive regions of the liver. Among the transcripts associated with phosphatidylcholine biosynthesis, upregulation of PLA2G4C mRNA was most pronounced following HCV infection. Activation of the transcription factor NF-κB and upregulation of c-Myc were important for activation of PLA2G4C transcription by HCV infection and expression of the viral proteins Core-NS2. The amount and size of lipid droplets were reduced in PLA2G4C-knockout cells. Inhibition of NF-κB or c-Myc activity suppressed lipid droplet formation in HCV-infected cells. HCV infection promoted the stabilization of lipid droplets, but this stability was reduced in PLA2G4C-knockout cells. Overexpression of PLA2G4C decreased the levels of phosphatidylcholine species in the lipid droplet fraction and led to lower levels of key factors involved in lipolysis (breakdown of triglycerides into glycerol and free fatty acids), such as ATGL, PLIN1 and ABHD5 on the lipid droplets. Conclusions: HCV infection markedly increases PLA2G4C expression. This may alter the phospholipid composition of the lipid droplet membrane, leading to stabilization and enlargement of the droplets. Impact and implications:: The involvement of phospholipid metabolism pathways in the pathogenesis of hepatitis C virus (HCV)-related liver diseases remains unclear. We found that PLA2G4C expression is upregulated through NF-κB and c-Myc activation upon HCV infection, and this upregulation is associated with a decrease in phosphatidylcholine species. The increased expression of PLA2G4C resulted in changes in the phospholipid composition of lipid droplets, led to the dissociation of lipolysis-related factors from the lipid droplet surface and the accumulation of lipid content within the droplets. These findings suggest that the disruption of the phospholipid metabolism pathway caused by HCV infection may contribute to the development of HCV-associated fatty liver. It would be interesting to determine whether alcohol- and/or metabolic dysfunction-associated steatohepatitis are also associated with increased PLA2 activity, altered phospholipid composition and decreased levels of ATGL and its cofactors in lipid droplet membranes.